Role of Enhancer of zeste on the production of Drosophila melanogaster pheromonal hydrocarbons. - Wicker-Thomas, C.; Jallon, J. (Naturwissenschaften, 2000)
In a search for genes controlling the production of Drosophila melanogaster contact pheromones, the gene Enhancer of zeste [E(z)] was found to be one player. Flies mutant for either the amorphic or the antimorphic allele of E(z) showed a similar hydrocarbon phenotype as those with the overlapping Df lxd(15) deficiency: decreased amounts of total hydrocarbons and especially unsaturated ones in both sexes. The decrease in the level of D. melanogaster female sex pheromone 7,11-heptacosadiene was dramatic and was correlated with an increase in 7-heptacosene. Females mutant for a gain-of-function allele had increased amounts of total hydrocarbons with wild-type proportions of dienes. Thus the E(z) gene seems to affect hydrocarbon biosynthesis, especially its desaturation steps and even more so the female-specific desaturation step transforming 7-monoenic fatty acids to 7,11-dienic ones and leading to female pheromones.